Drivers of Tidal Flooding and Coastal Vulnerability in the Riau Islands, Indonesia: A Time-Series Analysis (2022-2024) - Latifah, Laila; Pranowo, Widodo Setiyo; Mujiasih, Subekti; Ratnawati, Herlina Ika; Hatmaja, Rahaden Bagas; Suhana, Mario Putra; Setiyadi, Johar; Lelalette, Johanis Dominggus; Izzaturrahim, Muh. Hafizh; Ismail, M. Furqon Azis; Syah, Achmad Fachruddin; Ryanto, Fauzan Novan; Setiyono, Heryoso; Helmi, Muhammad (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
The Indonesian Maritime Continent is highly vulnerable to climate variability and change, as exemplified by tidal flooding events in the Riau Islands from 2022 to 2024. This study aimed to analyze the characteristics of sea level dynamics and anomalies associated with tidal flooding (rob) and identify the contributing factors. Data on tidal flooding events were gathered from press and online social media reports, while additional information on significant wave height, ocean currents, and wind was obtained from the CMEMS (Copernicus Marine Environment Monitoring Service) Marine Copernicus archives (marine.copernicus.eu). Observational data from tide gauge stations were also accessed via the IOC sea level monitoring system (ioc-sealevelmonitoring.org). The findings revealed a high probability of tidal flooding during the north wind season, particularly in January and February. Notably, tidal elevations during flooding events reached 3.06 m on January 25, 2023, 3.00 m on February 21, 2023, and 3.09 m on February 12, 2024. These events were driven by a combination of oceanographic and atmospheric factors, including high tidal ranges during spring tides, strong wind speeds averaging 19.04 to 21.43 knots in January–February 2023 and 18.65 knots in February 2024, dominant southward current patterns, and significant wave heights reaching up to 1.08 m. The alignment of the sun, moon, and earth during full and new moon phases amplified gravitational forces, causing elevated sea levels. Furthermore, strong winds during the north wind season contributed to higher wave heights, intensifying flooding impacts. Analysis of current patterns indicates that the highest speeds were recorded during the northern wind season, specifically in January and February, which coincides with the tidal flooding events. The currents predominantly moved southward, aligning with the wind direction during this season. This study reveals oceanographic and atmospheric interactions driving tidal flooding, offering insights for mitigation and adaptation to enhance resilience in vulnerable coastal regions.